Cyclic tests of four two-story narrow steel plate shear walls?Part 1 Analytical studies and specimen design. - Tsai, Keh-Chyuan
This study consists of two parts. In this two-part research, four two-story narrow steel plate shear walls (SPSWs) were cyclically tested at the Taiwan National Center for Research on Earthquake Engineering in 2007. This paper, Part 1, proposes a capacity design method for the first-story boundary column of the SPSW to ensure that the plastic hinges form at the column bottom ends when the SPSW develops the plastic mechanism. The design method was developed based on the superposition method considering the frame sway action and the panel force effects of the SPSW. Restrained steel plate shear wall (R-SPSW) studied herein adopts pairs of the horizontal restrainers sandwiching over both sides of the infill panels and connected to the boundary columns. Analytical studies on four SPSW example designs using nonlinear finite element (FE) models and the simplified strip models confirm that the restrainers could also effectively reduce the column force demands and allow the infill panel to stretch more uniformly. In addition, the FE analytical studies verify the effectiveness of the proposed column capacity design method and the seismic design recommendations for the restrainer. This paper introduces the designs of the four narrow SPSW specimens, presenting the selections of the boundary beams and columns, the designs of the beam-to-column connections and the construction details of the restrainers. The experimental results, key observations and the design implications are reported in the companion paper.
Keywords: Steel plate shear wall (SPSW).; Restrained steel plate shear wall (R-SPSW).; Capacity design